EFEKTIVITAS MGMP DALAM PENINGKATAN PROFESIONALISME GURU MATA PELAJARAN UMUM DI MTS - Lisaâ€™diyah Maâ€™rifataini (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2014)
This research is to identify the effectiveness of the course teachersâ€™ consultation â€œEfektifitas Musyawarah Guru Mata Pelajaranâ€ (MGMP) in developing the professionalism of the general course teachers in Madrasah Tsanawiyah (MTs). This research uses mixed method approach with description analysis as its presentation. The chief of MGMP appears as the correspondent which has become a member of MGMP, kasiMapenda, and the head of madrasah also the supervisor of the establishment of MGMP in seven provinces. This research applies the stratified random sampling as its method sampling. The result of this research shows the lack of effectiveness inconsulting the general course teachersâ€™ professionalism based on the goal and structure of MGMP. This is based on the resulting discovery that identifies only the component of the MGMP towards the teachersâ€™ needs appears to be effective compared by the whole six other components involved.